Transgenerational effect of Afidopyropen on Bemisia tabaci Gennadius (Homoptera: Aleyrodidae) - Muhammad Salman Shafi; Naeem Iqbal; Muhammad Nadir Naqqash; Shafqat Saeed; Muhammad Usman; Allah Ditta Abid; Muhammad Sohail Shahzad; Hasan Riaz; Muhammad Amjad Bashir; Reem Atalla Alajmi (Scientific Reports, 2023)
Abstract Bemisia tabaci Gennadius (Homoptera: Aleyrodidae) is the most devastating insect-pest in cotton crop. It is vector of the cotton leaf curl virus (CLCV) and is responsible for huge losses to cotton industry in Pakistan and worldwide. It is mainly controlled by insecticides but the injudicious use of insecticides has resulted in insecticide resistance and population resurgence in addition to various harmful effects on the humans, non-target organisms and the environment. Transgenerational studies are very helpful to choose a best insecticidal option. In the current study, age-stage two-sex life table analysis was used to identify transgenerational effects of sublethal doses of afidopyropen. The adults of B. tabaci were treated with three concentrations of afidopyropen i.e., LC10, LC30 and LC50. The results indicated significant changes in the progeny i.e. the fecundity decreased in treated population; and female and male longevity of their progeny were more in control as compared to treated populations. Similarly, population parameters like intrinsic rate of growth (r), net reproductive rate (R 0) and limiting rate of growth (λ) were significantly decreased in the treated adult progeny with values of 0.08–0.11, 4.85–7.46 and 1.09–1.12 per day, respectively. Based on the reduced biotic potential, afidopyropen can be suggested as an effective alternative option for the management of B. tabaci.